EXPLORING THE FACTOR OF SERVICE QUALITY (CASE STUDY AT PT. PLN SOUTH MAKASSAR) - Arie Pratama; Haris Maupa; Andi Nur Baumassepe (Paulus Journal of Accounting (PJA), 2023)
This study aims to explore the factors that shape service quality. This research was conducted by combining several existing dimensions of service quality and looking for gaps in the constructs of these measurementdimensions which were adjusted to the conditions in the object of research. The sample in this study were PLN customers in the UP3 South Makassar area. This research is quantitative research using confirmatory factoranalysis 1st order. The results showed that the 5 dimensions used in this study (tangibility, reliability, responsiveness, assurance, empathy, and technology) proved to be able to be used as service quality measurement factors.